Bluebirds and Other Cavity-Nesting Birds: Youth Project Book - Loretta Rodriguez; Joy Jordan; Mark E. Hostetler; Christina Packard; Jessica Kochert (EDIS)
4HWLM20, a 68-page illustrated project book by Loretta Rodriguez, Jessica Kochert, Joy Jordan, Christina Packard, and Mark Hostetler, helps youth aged 11-13 become careful and knowledgeable observers of bluebirds and other cavity-nesting birds. Youth will learn to create a habitat that promotes the health and safety of local cavity-nesting birds. Finally, the project guides youth to explore and learn about bluebird monitoring and data collecting programs. Includes references. Published by the Florida 4-H Youth Development Program, January 2010.